“Is our choice of empirical antibiotics appropriate for patients with methicillin resistant Staphylococcus aureus in breast abscess?” - Lodhi, Nazia (Iran J Microbiol, 2018)
BACKGROUND AND OBJECTIVES: Breast abscesses remain as one of the most common reasons for females to come for a surgical consult. This retrospective cohort study includes both lactating and non-lactating females with breast abscesses. Due to changing trends in bacteriology of organisms, we need to reconsider our empirical choices of antibiotics. In our study, the main causative organism in breast abscess was Staphylococcus aureus with predominant species being MRSA. MATERIALS AND METHODS: This is an analytical review of all breast abscesses treated in a single center from 2012 to 2015. This study included bacterial cultures, antibiotic sensitivities and resistance pattern in breast abscesses. RESULTS: 268 patients were included in the study. 143 (53.4%) were Lactational abscesses and 125 (46.6%) were non-Lactational abscesses. 169 (63.0%) harbored S. aureus in which 86 (50.8%) were MRSA. MRSA was the predominant organism in the Lactational group while non-Lactational group had no growth or other organisms in culture in this study. Other growing organisms were Klebsiella pneumoniae, Bacteroides, Pseudomonas, Streptococcus species and Mycobacterium tuberculosis. On comparative analysis, MRSA showed statistically a significant difference with p<0.0001, when it comes to predominant growth in lactating mothers. First line prescribed empirical antibiotics received by the patient, which is amoxicillin clavulanate, is mostly resistant. It is recommended that the institutional antibiogram targeted treatment be offered to patients with breast abscess. We also recommend ciprofloxacin with clindamycin as initial empirical therapy. CONCLUSION: MRSA was the most common organism seen in breast abscesses. Our first line treatment of antibiotics was resistant. Clindamycin and ciprofloxacin should be the preferred 1(st) choice for treatment.